Training and Sport Performance of the 11-12 Year Old Athletes in Rhythmic Gymnastics - Renata Rutkauskaitė; Antanas Skarbalius (Lithuanian Sports University, 2018)
The efficacy of athlete's sport performance depends on the targeted training in certain periods, organization, management, individual adaptation of an athlete to the loads of training and competitions. The aim of this study was to establish the key indices of training and fitness optimization of 11-12 year old athletes in rhythmic gymnastics. The experiment resulted in modeling five different training programs and establishing the structure of the content of the training programs, as well as athletes' sports performance (athletic, technical and mental). The training loads protocols registered the time for choreography, element mastering, competitive routines and athletic training in eachtraining session. The efficacy of the training programs was established registering the realization of competitiveactivities under competitive conditions, according to the number of points received by the gymnast of each training program, according to the place won (the points awarded in the descending order). Athletes in different training programs trained diversely - significant differences (p < 0.001) occurred in the indices of training loads (from 8.3 to 14.7 hours a week), days of training (from 207 to 295 days a year) and training content. Body composition indices of athletes did not differ statistically significantly (p > 0.05). Statistically significant differences (p < 0.05) were found in the indices of explosive strength and muscular, specific endurance,  movement abilities and the integral index of athletic fitness. The program where choreographic training (28.2%) dominated was the most efficient. Effective sports performance of 11-12 year old athletes in rhythmic gymnastics was greatly affected by all indices of technical fitness (r = 0.723 ÷ 0.883), integral index of athletic fitness (r = 0.881), explosive strength (r = 0.739), and endurance (r = 0.700). Significant changes of results could be explained not only by the changes in choreographic training, but also in the components of specific training, especially the time for mastering competitive routines (r = 0.717) and optimal training loads (11.5 ± 2.8 hours per week). The impact of body compositions indices, comparedto other factors, was not great (r = 0.478 ÷ 0.557) on the sports performance of athletes at this age. Keywords: rhythmic gymnastics, training, fitness.